Counseling persons of African descent raising the bar of practitioner excellence - Parham, Thomas A. (Thomas Anthony), 1954-; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2002)
This title provides an in-depth analysis of the counselling literature pertaining to African American clients. Topics discussed includes understanding personality and its measurement and African centered psychology.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Mental health counseling; African Americans -- Counseling of; Electronic books